Relationship between depression and anxiety with social isolation due to confinement in older adults - Chávez-Negrete, Luis A. (2021)
Introduction: as a consequence of the social isolation associated with COVID-19, depression and anxiety are two of the most frequent affective disorders in the elderly. Objective: To determine the relationship between depression and anxiety with social isolation in older adults in a first level care clinic. Material and methods: An observational descriptive cross-sectional study was carried out in patients 65 years and older, of both sexes, in social isolation due to confinement. A validated questionnaire was applied for the diagnosis of anxiety and depression, as well as another with questions about social isolation and sociodemographic variables. The Mann-Whitney and Kruskall Wallis U statistical tests were used, with a significance level of 0.05. SPSS program. Version 26. Results: 286 older adults were included, with an average age of 70.6 years, 54.2 % belonged to the female sex. Regarding the social isolation, 73.4 % reported a lack of relationship with their friends. The average score of the questionnaire was 45.06 (95% CI: 43.4% - 46.6%). Only 25.3 % did not present neither anxiety nor depression, and in 51.1 % some type of depression was identified. Regarding social isolation and its relationship with anxiety and depression; statistical significance was obtained in all questions. Conclusion: the social isolation of the elderly due to confinement by SARS-CoV2, was related with statistical significance to both anxiety and depression, while noting that in 75% of the patients one of the two conditions was presented.